Transport Charge of Gallium Arsenide Films Synthesized on Polycrystalline Silicon by Ionics Ablation; EFRE-2014: 12th International Conference on Modification of Materials with Particle Beams and Plasma Flows - Kabyshev A. V. Alexander Vasilievich; Konusov F. V. Fedor Valerievich; Remnev G. E. Gennady Efimovich; Pavlov S. K. Sergey Konstantinovich (2014, 2014)
Title screen